The Affecting Factors of Nurses’ Compliance in Nursing Documentation - Nyarmi; Dwi Wahyuni, Erna; Ni’mah, Lailatun (International Journal of Psychosocial Rehabilitation, 2020)
Background: the lack of nurses’ adherence in making nursing documentation will result in the decrease of quality and completeness of hospital records. The factor that mainly affects the nurses’ compliance is that not all nurses have similar knowledge and ability in making the documentation based on the specified rule. Aim To analyze the relation between nurses’ compliance and their knowledge, attitude, and motivation in making nursing documentation. Method: This study applied a descriptive analytical design with a cross-sectional approach, with 20 nurses as the respondents. The independent variable from this research is the predisposing factors, namely knowledge, attitude, and motivation. While the dependent variable is the compliance of nurses towards nursing documentation. The data were collected using questionnaires and analyzed using Spearman’s Rank Correlation Coefficient with p = 0.05. Result: Knowledge (r = 0.457) and attitude (r = 0.467) have a rather low correlation, while motivation has a sufficient correlation (r = 0.649) towards nursing documentation. Conclusion Knowledge, attitude, and motivation of nurses go in line with their compliance in nursing documentation. Through this study, nurses are expected to be able to improve their literature study in terms of nursing documentation or be more active in participating in any activity related to nursing documentation.